2018
DOI: 10.5114/amscd.2018.81057
|View full text |Cite
|
Sign up to set email alerts
|

WHOQOL-BREF survey of quality of life among dialyzed end-stage renal disease patients

Abstract: Introduction: Hemodialysis (HD) improves health and prolongs the life of end-stage renal disease patients, but simultaneously leads to emotional disturbances and impairs the quality of life (QOL). The study was conducted to evaluate the QOL of HD patients. The study was approved by the Regional Bioethical Committee (K.B.Cz.-0014/2017). Material and methods: The World Health Organization Questionnaire of QOL (WHOQOL-BREF) was used in this study with the formal agreement of the WHO. The associations between each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Lee et al suggested that a higher rate of independence from dialysis after ASCT may be related to shorter duration of dialysis before ASCT (< 6 months) and recommend ASCT as consolidation to the first-line therapy [10]. Dialysis independence is a key to the improvement of the quality of life [40,41]. Thus, it should be considered as an ultimate goal after ASCT in patients with advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al suggested that a higher rate of independence from dialysis after ASCT may be related to shorter duration of dialysis before ASCT (< 6 months) and recommend ASCT as consolidation to the first-line therapy [10]. Dialysis independence is a key to the improvement of the quality of life [40,41]. Thus, it should be considered as an ultimate goal after ASCT in patients with advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This self-report inventory contains 26 items divided into four domains: physical health, psychological health, social relationships, and environment. Additionally, two separate questions measure overall self-perception of quality of life and overall self-perception of health [ 18 , 19 , 20 , 21 , 22 ]. The items of the WHOQOL-BREF are rated on a 5-point Likert scale, and the domain scores are calculated on a scale of 0−20, where higher scores represent better quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…DRA may affect physical function and quality of life [6,8,13]. It has been suggested that DRA is associated with urinary incontinence, lower back pain, lack of trunk strength, body dissatisfaction and significantly impaired quality of life [6,10,11,14]. However, whether DRA actually causes these symptoms or coexists remains unclear [6].…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%